PENEGAKAN HUKUM TERHADAP PEMILIK BILLIARD YANG MENJADI LOKASI PERJUDIAN DI KABUPATEN TAPANULI UTARA - MANALU, KRISTINA; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Gambling crimes are often found in various community environments Tapanuli Utara District. The essence ic contrary to religion, morality and morality of Pancasil and dangerous society, nation and state and in terms of national intersts. The type of gambling that is widely trated in Tapanuli Utara Regency is the of Billiards. That Billiard activities is a very profitable business activities. The author intends to discuss the arrest of pool owners are not optimal. The purpose of this study wa study law enforcement carried out by law enforces against the hall of billiards in Tapanuli Utara District and violations in the enforcement and eradication of types of hall of billiards crime in Tapanuli Utara District. The research was conducted in North Sumatera Tapanuli Utara District, which conducted research on the Tapanuli Utara Resort Police, and community Tapanuli Utara District. The technique used in collecting data is obersevation, interview and literature study.From the research is conclusive that the law enforcement enforcement of billiards gambling crimes against the Tapanuli Utara District law enforcement agents are yet to be fully maximally, and there has not been a specific effort from law enforcement officials to provide the billiards gambling. In law enforcement by the Tapanuli Utara Resort Police are still focused on the existence of reports directly from the public. And the obstacles in the enforcement and eradication of criminal acts of gambling in the North Sumatera Tapanuli of two factors, namely internal factors and external factors. Internal factors are the inhibiting factors that come from within the body of law enforcement officers, namely from the Tapanuli Utara Resort Police Agency which consists of: constraints to law enforcement officers, constraints on facilities and infrastructure, professionalism of the law enforcement officers, low knowledge of law enforcement officers. And external factors are inhibiting factors that come from outside the body of the Tapanuli Utara Resort Police, which include: the presence of person who protect the criminal gambling gambling, community constraints, regulatory constraints.Keywords: Law Enforcement-Crime-Gambling-Billiards